Flexural Behavior of Graphite Tailings RC Beams in Chloride Environment - Bo-Ya Feng; Xun-Guo Zhu; Hong-Chun Xia; Lin Yang; Te Xie (Advances in Civil Engineering)
This paper investigates the mechanical properties of graphite tailings concrete beams under various curing environments. The results show that the concentration of graphite tailings has an important influence on the mechanical properties of concrete. Finally, the bending characteristics of the beam and the modified bearing capacity calculation formula are obtained, which provides a theoretical basis and the reference value for the construction of green building materials. Through research, the main innovations and main findings of this paper are as follows: (1) In the three kinds of concrete experimental environment, the fracture load and ultimate load of concrete beams with graphite tailings replacement rate of 20% are the largest. (2) In the three kinds of concrete test environment, when the concrete test beams under the same load, with the increase of graphite tailings replacement rate, the mid-span deflection of concrete beams showed a trend of decreasing first and then increasing. When the replacement rate of graphite tailings sand is 20%, the mid-span deflection of the test beam is the smallest. (3) Through experiments, it is found that the normal section bearing capacity of graphite tailings concrete beams after chloride salt erosion conforms to the plane section assumption. After chlorine salt erosion, the strain of the longitudinal tensile steel bar of concrete beams with different graphite tailings sand replacement rates is the same as that of ordinary concrete beams, and the slope of the strain curve is the same, showing a linear trend. The experimental results show that the replacement rate of graphite tailings sand has an insignificant effect on the strain of steel bars. (4) The Gauss function is used to fit the experimental value of normal section bearing capacity of concrete beam, and the calculation formula of normal section ultimate bearing capacity of graphite tailings sand concrete beam under chloride environment is established. The research results of this paper have significant reference value for the study of mechanical properties of graphite tailings sand concrete components.